NKT cells promote Th1 immune bias to dengue virus that governs long-term protective antibody dynamics - Choi, Youngjoo (2024)
NKT cells are innate-like T cells, recruited to the skin during viral infection, yet their contributions to long-term immune memory to viruses are unclear. We identified granzyme K, a product made by cytotoxic cells including NKT cells, as linked to induction of Th1-associated antibodies during primary dengue virus (DENV) infection in humans. We examined the role of NKT cells in vivo using DENV-infected mice lacking CD1d-dependent (CD1ddep) NKT cells. In CD1d-KO mice, Th1-polarized immunity and infection resolution were impaired, which was dependent on intrinsic NKT cell production of IFN-γ, since it was restored by adoptive transfer of WT but not IFN-γ-KO NKT cells. Furthermore, NKT cell deficiency triggered immune bias, resulting in higher levels of Th2-associated IgG1 than Th1-associated IgG2a, which failed to protect against a homologous DENV rechallenge and promoted antibody-dependent enhanced disease during secondary heterologous infections. Similarly, Th2 immunity, typified by a higher IgG4/IgG3 ratio, was associated with worsened human disease severity during secondary infections. Thus, CD1ddep NKT cells establish Th1 polarity during the early innate response to DENV, which promotes infection resolution, memory formation, and long-term protection from secondary homologous and heterologous infections in mice, with consistent associations observed in humans. These observations illustrate how early innate immune responses during primary infections can influence secondary infection outcomes.